Research Advances in Tetraspanins in Colorectal Cancer - Chengwei LIU; Kunyang WANG; Zhen HU; Yaoping LI (Zhongliu Fangzhi Yanjiu)
The tetraspanins are closely associated with the development and therapeutic prognosis of colorectal tumors. These proteins play a role in cell proliferation, metastasis, and invasion, regulate apoptosis and autophagy of colorectal tumor cells. affect immune escape by releasing exosomes, intervening the epithelial-mesenchymal transition process, and altering the tumor microenvironment, and enhance tumor stemness through specific pathways. This paper reviews the mechanisms and current research regarding the status of tetraspanins in colorectal cancer, aiming to improve early diagnosis and providing valuable insights for treatment strategies.